1994
DOI: 10.1007/bf00021290
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuation of planktonic rotifers in Azibo reservoir (Portugal)

Abstract: The rotifers of the recently-commissioned Azibo reservoir were studied during two years. The community was similar to that of other Portuguese reservoirs with Keratella cochlearis, Polyarthra spp., Asplanchna priodonta and Collotheca pelagica dominant, although densities varied strongly. Maximum rotifer density was 640 ind 1-' in 1987 and 315 ind I-' in 1988. During the first year two density peaks were observed, while in the second year fluctuations were irregular. Phytoplankton availability was considered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…Rotifera formed 91.82% of the total zooplankton density; its maximum density was recorded during spring, and this is due to the increasing trophic status. Similar observation was reported in the studies of Vasconcelos (1994) and Abdel Aziz and Aboul Ezz (2004) who mentioned that, the availability of phytoplankton is considered to be the main reason for the fluctuation of rotifer density. Moreover, the current finding coincides with the report of Paturej (2008) who showed that the density of rotifers increases significantly with increasing trophic state elsewhere.…”
Section: Discussionsupporting
confidence: 89%
“…Rotifera formed 91.82% of the total zooplankton density; its maximum density was recorded during spring, and this is due to the increasing trophic status. Similar observation was reported in the studies of Vasconcelos (1994) and Abdel Aziz and Aboul Ezz (2004) who mentioned that, the availability of phytoplankton is considered to be the main reason for the fluctuation of rotifer density. Moreover, the current finding coincides with the report of Paturej (2008) who showed that the density of rotifers increases significantly with increasing trophic state elsewhere.…”
Section: Discussionsupporting
confidence: 89%
“…Increasing densities in ponds may be attributed to high density of phytoplankton. This complied with Vasconcelos (1994), who concluded that the phytoplankton availability was considered the main reason for fluctuation of zooplankton density, although temperature and dissolved oxygen interference may also have played a role. But the low number of zooplankton in drains may be related to the decrease in nutrients concentration, where it covered with macrophytes and hence depriving the water from its nutrient and suppressing the phytoplankton growth and decreasing zooplankton.…”
Section: Hydrogen Ion Concentration (Ph)supporting
confidence: 85%
“…The 38 species found is a relatively low number in comparison with natural lakes (Virro 1996), but is common in deep reservoirs (De Manuel & Armengol 1993;Vasconcelos 1994;Devetter 1998bDevetter , 2004. Fluctuation of the diversity index does not show any strong trend apart from a regular decrease around the end of the year.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal fluctuation of individual species generally corresponds to their common habits (Vasconcelos 1994). However, typical population phases in many species, such as the start of population development or maxima, were synchronized through the years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation